Teacher Training And Continuing Professional Development: The Singapore Model - Chew, Lee Chin (Proceeding of International Conference on Teacher Training and Education, 2016)
This paper presents Singaporeâs initial teacher training and continuing professional development as apossible model of teacher education and preparation. Since the mid-1990s, several educational reforms andÂ initiatives have been introduced into Singapore education with the goal of equipping her young citizens withÂ knowledge and skills for a globalised economy and workforce, and for the challenges of the 21 st century.Â Teachers are the frontline of any educational endeavour, which means that teacher quality is paramount toÂ its implementation. Thus, the Ministry of Education invested heavily in building the teacher workforce andÂ enhancing its quality in pursuit of the desired educational outcomes. Increased and sustained teacherÂ recruitment enlarged the teacher workforce. Stringent criteria were used to select suitably qualifiedÂ applicants who went through intensive pre-service teacher training at Singaporeâs sole teacher trainingÂ institute, the National Institute of Education. Several policies were put in place to enable in-service teachersÂ to continually develop and upgrade themselves professionally. For instance, every teacher was entitled toÂ 100 hours per year of professional development. A multi-prong approach was deployed to encourageÂ teachersâ participation in professional training and development. These included workshops or short coursesÂ for deepening knowledge of subjects taught and for enhancing pedagogical skills, and conference or seminarÂ attendance for sharing teaching practices and broadening experiences. Teachers were also initiated intoÂ âlife-long learningâ with various sponsorship schemes to pursue masters or doctoral level studies. On theÂ belief that an educational system is as good as the quality of its teachers, this paper concludes with aÂ discussion of Singapore educationâs continuing journey towards innovations in teacher development.